Pengaruh Kompensasi, Motivasi, Lingkungan Kerja, Serta Stres Kerja Terhadap Kinerja Karyawan - Sumaraw, Rifka Ervina (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
The objective of this research is to discover the influence of compensation, motivation, work environment, and work stress on employee performance. Research instrument is questionnaire in the form of structured questionnaire. Closed questionnaire is used as it is question models with answer choices provided so that respondents only choose from alternative answers according to their opinion or choice. Those closed questions explain respond from respondents on variables of compensation, motivation, work environment, work stress, and employee performance. Analysis method is multiple linear regression analysis. The result of research shows that compensation, motivation, work environment, and work stress influence employee performance, partially and simultaneously at PT. BCA KCU Manado. It is suggestedÂ  that company always raises salary, facilitates employees to strengthen employees relationships, create comfortable work environment for its employees, develops skills and abilities of employees to improve their performance and thus profitable to the company